Terorisme Tidak Identik Dengan Islam - Mudemar A Rasyidi (JURNAL MITRA MANAJEMEN, 2016)
AbstractTerorism : is a criminal act, which is international, national and local in nature. Both organized and collectively / in groups, and individually. Both trained and untrained. Intentionally posing threats with violence and violent acts. With intention to commit a crime that may give rise to unrest, panic for a group of people, or many people, or bringing about fear or committing an act that may harm a group of people or many people, or resulting in insecurity for the people, by employing light weaponry or heavy weaponry or alutsista (mobilization of main defense equipment), or committing and act that may bring about damages against properties or neighborhood and public or committing an act thay may cause damages on private verhicle or public transportation or warfare equipmet, or homes / residences private owned or government owned, or damaging and/or destroying hospitals, official residences, offices, building owned by privates or owned by government, hotels, both owned by privates and owned by government, bringing about damages to or destroying private owned and government owned installations, damaging / destroying all types of equipments used for public or government, both civil and military. Or destroying properties, or occupying/taking over or seizing any thing or also causing casualities of properties or lives against the law. As well as committing acts that put resources at danger, nationally and internationally, on behalf of individuals, tribes, races, ethnics, groups, or religions. And the perpetrators can be charged with capital punishment or lifetime imprisonment, or sentences in jail minimin for 4 (four) years, and maximum for 20 (twenty) years. Keywords: Holy Koran Nul-Karim, Al-Hadist, Islamic Law, Eradication of Criminal Act of Terorism Law (Law No. 15 of 2003 in conjunction with the Government Regulation in Lieu of Law No. 1 of 2002) various sources Local, National and International in regard to Terrorism, and so forth.